Cold war deceptions : the Asia Foundation and the CIA - Price, David H., 1960- (University of Washington Press, 2024)
During the early Cold War, the Central Intelligence Agency created dozens of funding fronts to support work that aligned with CIA goals, from clandestine operations and research to liberal anticommunist programs. While investigative journalists and congressional inquiries exposed many of these fronts, little is known about their daily internal workings. With a specific focus on the 1950s and 1960s Asia Foundation, Cold War Deceptions provides a rare view into the bureaucratic functioning of a covert operation in which most employees did not know they were working for the CIA. Drawing on the foundation's extensive surviving archival records and thousands of pages of declassified CIA documents, David H. Price examines how the foundation, secretly created and funded by the CIA, tried to shape Asian political, economic, intellectual, and cultural developments during the early years of the Cold War. Uncovering how unwitting scholars were used to support pro-American and anticommunist positions, Price considers how political forces shaped disciplinary knowledge and how these past events connect to the present.
Keywords: United States. -- Central Intelligence Agency.; Asia Foundation.; Espionage, American -- Asia.; Anti-communist movements -- United States.; Anti-communist movements -- Asia.; Propaganda, American -- Asia.; Cold War.; United States -- Foreign relations -- Asia.; Asia -- Foreign relations -- United States.; Asia -- Foreign relations.; Espionnage américain -- Asie.; Anticommunisme -- États-Unis.; Anticommunisme -- Asie.; Propagande américaine -- Asie.; Guerre froide.; États-Unis -- Relations extérieures -- Asie.; Asie -- Relations extérieures.; POLITICAL SCIENCE / Intelligence & Espionage